EFEKTIVITAS PELAKSANAAN MUSYAWARAH PERENCANAAN PEMBANGUNAN DI KELURAHAN BESUSU TENGAH KECAMATAN PALU TIMUR KOTA PALU - Sunarti Sunarti (Katalogis, 2015)
The research aimed to determine the effectiveness of the development in central Besusu village, East Palu sub-district, Palu. Effectiveness is an activity to achieve the goal by using available  infrastructure and resources. Referrred to Rhicard M. Steers, to measure the effectiveness of development activities in the Village Council Central Besusu consists of three (3) aspects, including, Goals; Integration; and Adaptation. The research  used a qualitative method of data analysis was the qualitative analysis model. There were 7 informants selected by technique  purposive sampling. The results of the research indicated that the effectiveness of musrenbang implementation in central Besusu Village, quite effective. However, the achievement of the objective aspect, there were some suggestions less accommodated, in the process of musrenbang implementation can be stated that it was worst towards the musrenbang goal itself. While the two (2) other aspects that intergation and adaptation, has been running well based on the list of priority program activities of Development Planning Meeting in the Village Central Besusu in 2014.